Interferência, resistência a inseticidas e sinergismo entre feromônio e voláteis de planta no bicudo-do-algodoeiro - Marra, Sharrine Omari Domingues de Oliveira (2019)
This work aimed to provide adequate parameters for an efficient management of the cotton bollweevil (A. grandis grandis), by evaluating the effect of volatile compounds of cotton, with the synthetic pheromone (grandilure®), and in the pheromone trap attractiveness in the field. A survey and mapping of the risk of control failure by insecticides used against this pest species (malathion and beta-cyfluthrin) and its sublethal effects on the ability to release and perceive pheromone and reproductive capacity were also assessed. The traps showed greater attractiveness, correlating with the presence of adults in the crop during the cotton reproductive stage. Although insecticide resistance was not detected, the sulethal insecticide impact was relevant. Males and females exposed to insecticides lost their ability to recognize the pheromone making the matingdifficultand compromising pheromone trap monitoring. The insecticides affected thethe fertility table parameters leading to a decrease in population growth. These results are importantfor bollweevilintegrated management allowing optimal use of pheromone traps during the coton reproductive period and adjusting the correlation between capture and loss in field under insecticide use.